The burial of Menippus: Hidden meanings in the paratexts to Thomas More's Utopia in Spanish Córdoba 1637 - Vibeke Roggen (Acta ad Archaeologiam et Artium Historiam Pertinentia)
Thomas More’s Utopia (1516) describes an ideal state – a clever way of criticizing the existing state without saying so explicitly. Utopia appeared in many editions both in the original Latin and in translation to various languages in the early modern period; the first translation into Spanish was published in 1637. The Córdoba 1637 edition has left out book 1 but contains many paratexts. The paper reads the paratexts, and the quotations in classical languages in particular, as a sort of hidden message in a Spain marked by the Inquisition and literary censorship. The famous poet Francisco de Quevedo is seen as a central figure in a local intellectual circle behind the edition.